Bridging nutrition education and community engagement: a healthy cooking demonstration program - Yahya, Hanis Mastura; Malek Rivan, Nurul Fatin; Abd. Talib, Ruzita (Universiti Teknologi MARA, Kedah, 2024)
Obesity rates in Malaysia are alarmingly high, with over 50% of adults being overweight or obese. Effective health education interventions are crucial to address this public health challenge. Cooking demonstrations have proven to be an effective tool for delivering health messages and encouraging healthier eating habits. This study evaluated a student-led healthy cooking demonstration program designed to empower the targeted communities with nutrition knowledge and skills for healthier food preparation. The program involved collaborative planning between nutrition science students and their supervisors, including the development of healthy menus and program logistics. Students engaged with community representatives (kindergarten teachers, older adults, and university students) to further refine the program. In addition to cooking demonstrations, students developed and shared nutrition education materials followed by a question-and-answer session. Participant feedback was collected to assess program effectiveness. The hands-on cooking demonstrations were well-received, with participants expressing high satisfaction. This student-led initiative demonstrates the potential of community-based cooking demonstrations to effectively promote healthier food choices and empower individuals with practical nutrition knowledge. The program also provided valuable experiential learning opportunities for future nutrition professionals. This model holds promise for broader implementation to address the growing issue of obesity in Malaysia.